2021
DOI: 10.3390/plants11010087
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Characterization of the Manoor Valley’s (Lesser Himalaya) Vegetation from the Subtropical-Temperate Ecotonal Forests to the Alpine Pastures along Ecological Variables

Abstract: Plant species are distributed in different types of habitats, forming different communities driven by different sets of environmental variables. Here, we assessed potential plant communities along an altitudinal gradient and their associations with different environmental drivers in the unexplored Manoor Valley (Lesser Himalaya), Pakistan. We have implemented various ecological techniques and evaluated phytosociological attributes in three randomly selected 50 m-transects within each stand (a total of 133) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that temperature and precipitation sustain the greatest impact on the distribution of Daphne mucronata species. Previous studies reported that soil variables, altitude, slope, aspect, and angle had a strong effect on species richness and plant distribution [ 29 , 30 ]. Generally, in mountainous areas, topographic characteristics, such as elevation, slope, and aspect, are the main factors influencing vegetation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that temperature and precipitation sustain the greatest impact on the distribution of Daphne mucronata species. Previous studies reported that soil variables, altitude, slope, aspect, and angle had a strong effect on species richness and plant distribution [ 29 , 30 ]. Generally, in mountainous areas, topographic characteristics, such as elevation, slope, and aspect, are the main factors influencing vegetation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The Pielou's evenness index value was led by the CIC community (0.97). Many researchers reported that the physicochemical properties influence plant species richness [90] and evenness [91].…”
Section: Discussionmentioning
confidence: 99%
“…This Himalayan part of Pakistan possesses a rich flora due to the fact that this part of country remained undisturbed by man for a long period; this enabled many species to survive and to evolve 47 . Even across short distances, the flora varies greatly 48 , with a high degree of resource seasonality 49 , 50 , 122 and diversity in both species 42 , 48 and communities 51 .…”
Section: Methodsmentioning
confidence: 99%